Improve Text Writing Skills Student Poetry using Image Media - Solahudin; Teti Sobari (IKIP Siliwangi, 2024)
This research focuses on the influence of image media on the ability to write poetry texts. In this research, qualitative descriptive research was used. The aim of this research is to find out whether the image media used can help and make it easier for students to improve their poetry text writing skills and see the differences in students' abilities before and after using image media in learning Indonesian. The research target was 20 class VIII students at SMPN 1 Naringgul for the 2021/2022 academic year. This research was carried out using qualitative descriptive research methods. Researchers collected data using test instruments, interviews and observations. In practice, before and after the learning treatment, students are given a pretest and posttest. The results of the research carried out obtained a score for writing poetry texts with an average pretest of 55.4 and posttest of 81.7. The SPSS analysis results show a significance of 0.000<0.05 so that there is a difference between learning outcomes before and after treatment. The research results obtained show that the application of image media in learning to write poetry texts can increase in class VIII junior high school students.